2022
DOI: 10.3233/bpl-210132
|View full text |Cite
|
Sign up to set email alerts
|

The BDNF Val66Met Polymorphism is a Relevant, But not Determinant, Risk Factor in the Etiology of Neuropsychiatric Disorders – Current Advances in Human Studies: A Systematic Review

Abstract: Brain-derived neurotrophic factor (BDNF) is the brain’s most-produced neurotrophin during the lifespan, essentially involved in multiple mechanisms of nervous system development and function. The production/release of BDNF requires multi-stage processing that appears to be regulated at various stages in which the presence of a polymorphism “Val66Met” can exert a critical influence. Aim: To synthesize the knowledge on the BDNF Val66Met polymorphism on intracellular processing and function of BDNF. Methods: We p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Together, the literature on the role of the BDNF polymorphism is controversial and leaves many unresolved issues. It is, overall, consistent with the notion that the Val66Met polymorphism is relevant, but not determinant, as a risk factor for neuropsychiatric disorders [39].…”
Section: Plos Onesupporting
confidence: 88%
“…Together, the literature on the role of the BDNF polymorphism is controversial and leaves many unresolved issues. It is, overall, consistent with the notion that the Val66Met polymorphism is relevant, but not determinant, as a risk factor for neuropsychiatric disorders [39].…”
Section: Plos Onesupporting
confidence: 88%
“…Results from a human study indicated that metabolic stress downregulates the expression of BDNF but not concentrations of plasma BDNF [ 93 ]. An alteration in the pro-BDNF/BDNF ratio deriving from the rs6265 polymorphism might be important to consider [ 94 ]. A complete overview of this complex system is out of scope for this paper.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous research, we showed that the BDNF Val66Met polymorphism might negatively influence BDNF secretion by affecting different stages of its synthesis. It affects cleavage and trafficking processing of proBDNF throughout the secretory pathways, resulting in a less efficient distribution of BDNF in the dendrites and axons or its activity-dependent release from synaptic terminals [31,32]. the influence of BDNF on stroke outcomes was first reported in patients of haemorrhagic stroke (31 Met carriers and 65 Val homozygous) investigated by Vilkki et al [33] when they noticed that Met carriers showed inferior learning and memory capability one year after stroke (table 1).…”
Section: Influence Of Bdnf Val66met (Rs6265) Polymorphismmentioning
confidence: 99%
“…It came to our attention that, whereas the common Val66Met polymorphism in BDNF gene is reported to affect several processes of the protein synthesis [32], this is not directly reflected in the circulating serum levels [29,31]. this leads to the interpretation that a slight misfunctioning in such an essential protein for the proper neuronal function is tolerable, although it does represent a vulnerability to the development of neuropathological conditions.…”
Section: Highlights and Final Considerationsmentioning
confidence: 99%